Polski gwarowy przysłówek przyboś, na przyboś i nazwisko Przyboś - Gałecki, Zygmunt (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The author proves that the etymology of the surname Przyboś came from the lexicalised adverb przyboś, na przyboś (walk), “to wear shoes on bare feet, with a bare foot, (walk) slightly barefoot”, that came from the adjective przybosy. The surname did not stem from either compound names such as Przybysław, Przybywój or from the verb przybyć, contrary to what has been stated in the historical and etymological dictionary Nazwiska Polaków by Kazimierz Rymut.